TINJAUAN FATWA DSN-MUI TERHADAP PENYITAAN BARANG JAMINAN PADA KSPPS AL-ANSHARI KOTA BUKITTINGGI - Muhammad Iqbal; Syukri Iska; Zulkifli Zulkifli; Khairina Khairina (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2023)
The purpose of this study was to find out or explore the procedures for confiscating collateral carried out at KSPPS Al-Anshari, Bukitinggi City and to analyze the juridical redemption of collateral confiscation carried out by KSPPS Al-Anshari, Bukitinggi City. The research method used by the author is qualitative research using field research with data collection techniques through interviews and documentation. Primary data sources consist of KSPPS Al-Anshari managers and employees. The data processing carried out here is qualitative. The results of the research that the author has done, First, the guarantee in the murabahah contract at KSPPS Al-Anshari is using property as collateral for debt, in practice the collateral in the financing is handed over to KSPPS Al-Anshari, but KSPPS Al-Anshari will give time leeway to customers to settle KSPPS Al-Anshari's debts, secondly regarding confiscated goods that are not in accordance with the fatwa because in the fatwa the confiscated goods should have been auctioned but the KSPPS Al-Anshari did not do so by making the confiscated goods an office operation. Islamic financing conditions in Indonesia in general are the Syafi'i (syafiiyyah) and Hambali (hanabillah) schools, that is, when the party responsible for the debt cannot pay it off, the debt is paid using assets or goods used as collateral or assets from the sale of assets used as collateral the. The benefits of collateral cannot be used as collateral (al-marhun), because the use of collateral is used up and damaged, therefore it cannot be used as collateral.